Case 3834: Ctenarytaina Ferris & Klyver, 1932 (Insecta, Hemiptera): proposed precedence over Eurhinocola Crawford, 1912 - Burckhardt, Daniel; Queiroz, Dalva Luiz de (Bulletin of Zoological Nomenclature, 2021)
The purpose of this application, under Article 23.9.3 of the Code, is to conserve the usage of the generic name Ctenarytaina Ferris & Klyver, 1932 for a genus of psyllids (Insecta, Hemiptera) from tropical and subtropical regions around the world. This name, which has been used in hundreds of works in recent decades, is threatened by a purported senior synonym, Eurhinocola Crawford, 1912. This genus was erected for Eurhinocola gravelyi Crawford, 1912 from Myanmar, a species that has not been mentioned since then in the literature except in catalogues. In 2020 the two genera were formally synonymized. Besides those already mentioned, only three other substantial publications on Eurhinocola have appeared, all between 1924 and 1937 and all pertaining to Eurhinocola eucalypti (Maskell, 1890). Using the senior synonym Eurhinocola would lead to nomenclatural instability and confusion, particularly with respect to two economically important species that are classified now in Ctenarytaina. We therefore request a reversal of precedence under the Commission’s plenary power, with Ctenarytaina to be given precedence over Eurhinocola whenever the two are considered to be synonyms.
Keywords: Nomenclature; taxonomy; eucalypt pests; invasive species; Insecta; Hemiptera; Psylloidea; Aphalaridae; Spondyliaspidinae; Ctenarytaina; Eurhinocola; psyllids; jumping plant-lice; blue gum psyllids; Australia